2008
DOI: 10.1159/000111558
|View full text |Cite
|
Sign up to set email alerts
|

Smart Drugs for Smarter Stem Cells: Making SENSe (Sphingolipid-Enhanced Neural Stem Cells) of Ceramide

Abstract: Ceramide and its derivative sphingosine-1-phosphate (S1P) are important signaling sphingolipids for neural stem cell apoptosis and differentiation. Most recently, our group has shown that novel ceramide analogs can be used to eliminate teratoma (stem cell tumor)-forming cells from a neural stem cell graft. In new studies, we found that S1P promotes survival of specific neural precursor cells that undergo differentiation to cells expressing oligodendroglial markers. Our studies suggest that a combination of nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 188 publications
(205 reference statements)
5
27
0
Order By: Relevance
“…This hypothesis is consistent with data from our laboratory showing that S1P and FTY720 protect a small population (≤5%) of neural precursor cells (NPCs), termed NPC2, from ceramide-induced apoptosis [358]. We routinely incubate EB-derived cells with S18 to eliminate residual pluripotent stem cells that will form stem cell-derived tumors if they contaminate the stem cell graft [82].…”
Section: Ceramide and S1p: Close Relatives But Conditional Antagonistssupporting
confidence: 82%
See 1 more Smart Citation
“…This hypothesis is consistent with data from our laboratory showing that S1P and FTY720 protect a small population (≤5%) of neural precursor cells (NPCs), termed NPC2, from ceramide-induced apoptosis [358]. We routinely incubate EB-derived cells with S18 to eliminate residual pluripotent stem cells that will form stem cell-derived tumors if they contaminate the stem cell graft [82].…”
Section: Ceramide and S1p: Close Relatives But Conditional Antagonistssupporting
confidence: 82%
“…This method has been recognized as a significant step toward safer stem cell therapy [359][360][361][362]. In contrast to the major population of nestin(+)/ PAR-4(−) NPC1 cells, NPC2 cells maintain the expression of PAR-4 and are eliminated by incubation with S18 [358]. These cells are protected by adding S1P or FTY720, which underlines the importance of S1P as a metabolically derived antagonist of ceramide ( Figure 8B).…”
Section: Ceramide and S1p: Close Relatives But Conditional Antagonistsmentioning
confidence: 97%
“…Ceramide induces the binding of prostate apoptosis response protein 4 (PAR-4) to the atypical protein kinase C [48] , an effect responsible for ceramide-induced apoptosis in cells showing elevated levels of PAR-4. As S1P antagonises ceramide-induced apoptosis [49] , it is likely to protect any cell type with high levels of PAR-4 from ceramide-induced apoptosis [50] . In mESCs, the endogenous levels of ceramide are low, increase upon EB formation until the early phase of NS/PC differentiation and finally decrease during the following steps of neural differentiation [48] .…”
Section: Lpa/s1p Signalling In Mouse Embryonic Stem Cellsmentioning
confidence: 99%
“…We have found that teratoma-forming rPS cells do not express the S1P receptor S1P1, which makes them vulnerable to ceramide or S18-induced apoptosis (Bieberich, 2008b(Bieberich, , 2010Bieberich et al, 2004). In contrast, ES cell-derived neural progenitor cells express S1P1.…”
Section: Induction Of Oligodendrocyte Differentiation By S1p and S1p mentioning
confidence: 96%
“…Many studies have shown that even when using similar protocols for the in vitro differentiation of ES cells, transplantation can lead to the formation of teratomas (Baker, 2009;Bieberich, 2008b;Blum &Benvenisty, 2008;Fong et al, 2010;Fujikawa et al, 2005;Lee et al, 2009;Vogel, 2005;. Teratomas are stem cell-derived tumors that are fatal if they grow in the brain or heart.…”
Section: Induction Of Apoptosis In Teratoma-forming Stem Cells By Cermentioning
confidence: 99%